Environmental geomorphology of Wadi Al-Batin, Kuwait: Unveiling natural and anthropogenic influences (Kuwait Journal of Science)
Wadi Al-Batin is an ancient valley that acts as the natural boundary between Iraq and Kuwait and is part of the larger Wadi Al-Rummah Basin in Saudi Arabia. Since the 1980s, human activities like military zones, oil fields, and camps have caused significant environmental changes in the area's geological, geomorphological, and hydrological conditions. This study investigates changes in the geomorphology, sedimentology, and topography of Wadi Al-Batin, land degradation and environmental changes caused by artificial landforms and natural factors and provides an update to the sedimentological map of Wadi Al-Batin. The study utilized field observations, geographical information systems (GIS), and remote sensing (RS) techniques to develop a geodatabase across various disciplines. A detailed map of the environmental geomorphological changes in Wadi Al-Batin was created using satellite imagery from 2000 to 2023 to provide up-to-date and precise information. The study also considered changes in the normalized difference vegetation index (NDVI) and normalized difference water index (NDWI) as indicators of environmental change. The results indicate that the surface deposits exhibited polymodal and trimodal modes (40% and 36%, respectively), were sandy and medium-coarse-grained, and showed variability in sorting, skewness, and kurtosis. They originated from the Upper Member of the Dibdibah Formation, were frequently fluvially reworked, and predominantly consisted of quartz with lower amounts of calcite. This study contributes to the preservation of environmental systems and assists decision-makers in protecting the rights of future generations to a sustainable environment. © 2024 The Authors